INBREEDING DEPRESSION AND EXPECTANT GENETIC ADVANCE IN F2 HYBRIDS FABA BEAN (Vicia faba L) - Shamil AL-Hamdany (Mesopotamia Journal of Agriculture)
The study aimed to evaluate the performance of hybrids and their parents for identify promising hybrids and the objectives to develop single cross hybrids in addition to estimate inbreeding depression , some genetic parameters , phenotypic and genotypic correlation for the studied characters. An experiment was conducted by using four varieties of faba bean (Vicia faba L.) viz., 1- French (Aguadulce) 2- Syrian (Shami) 3- Spain and 4- Holland , were Full diallel crossing carried out according to (Griffing 1956) first method (Model I) to produce F2-Hybrids of twelve single hybrid from self pollination of F1 hybrid during the growing season 2009/2010. The parents and F2 hybrid were planted by using Randomized Complete Block Design (R.C.B.D.) with three replications at vegetable field of the Horticulture and landscape design department , College of Agriculture and Forestry , Mosul University , during the growing season  2010/2011. Results showed that parents and F2S were significantly different for all the  studied characters , parent 1- French (Aguadulce) was found to be the best for green , dry pods yield , seeds yield and biological yield , whereas the hybrid (2×3) for the green , dry  pods yield and seeds yield , while the hybrid (2×1) for the biological yield. F2 hybrid exhibited a significant inbreeding depression for all the studied characters. A significant additive variance were found for all studied characters except date flowering and no.of seeds per pod. Narrow sense heritability was higher for: Plant height , no.of branches/plant , pod length , 100 seed weight ,  green , dry  pods yield and seeds yield , which indicated an additive gene action for these characters. Over dominance were found for: flowering , maturity date , no.of pods/plant , no.of seeds per pod and biological yield. Genetic advance expectant in F3 hybrid  were found for most studied characters , which indicates the importance of selection for improving these characters. The higher phenotypic and genotypic correlation were found between dry pods yield and seeds yield.